Cryoballoon ablation vs. antiarrhythmic drugs: first-line therapy for patients with paroxysmal atrial fibrillation. Issue 7 (17th March 2021) - Kuniss, Malte; Pavlovic, Nikola; Velagic, Vedran; Hermida, Jean Sylvain; Healey, Stewart; Arena, Giuseppe; Badenco, Nicolas; Meyer, Christian; Chen, Jian; Iacopino, Saverio; Anselme, Frédéric; Packer, Douglas L.; et al.
Abstract: Aims: Treatment guidelines for patients with atrial fibrillation (AF) suggest that patients should be managed with an antiarrhythmic drug (AAD) before undergoing catheter ablation (CA). This study evaluated whether pulmonary vein isolation employing cryoballoon CA is superior to AAD therapy for the prevention of atrial arrhythmia (AA) recurrence in rhythm control naive patients with paroxysmal AF (PAF). Methods and results: A total of 218 treatment naive patients with symptomatic PAF were randomized (1 : 1) to cryoballoon CA (Arctic Front Advance, Medtronic) or AAD (Class I or III) and followed for 12 months. The primary endpoint was ≥1 episode of recurrent AA (AF, atrial flutter, or atrial tachycardia) >30 s after a prespecified 90-day blanking period. Secondary endpoints included the rate of serious adverse events (SAEs) and recurrence of symptomatic palpitations (evaluated via patient diaries). Freedom from AA was achieved in 82.2% of subjects in the cryoballoon arm and 67.6% of subjects in the AAD arm (HR = 0.48, P   =  0.01). There were no group differences in the time-to-first (HR = 0.76, P  = 0.28) or overall incidence [incidence rate ratio (IRR)=0.79, P  = 0.28] of SAEs. The incidence rate of symptomatic palpitations was lower in the cryoballoon (7.61 days/year) compared with the AAD arm (18.96 days/year; IRR = 0.40, P  < 0.001). Conclusions: Cryoballoon CA was superior to AAD therapy, significantly reducing AA recurrence in treatment naive patients with PAF. Additionally, cryoballoon CA was associated with lower symptom recurrence and a similar rate of SAEs compared with AAD therapy. Graphical Abstract: